OPTIMALISASI PELAKSANAAN DISCHARGE PLANNING TERSTRUKTUR DAN TERINTEGRASI - Petrus Kanisius Siga Tage (Cintra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2018)
ABSTRAK Implementasi mengenai discharge planning merupakan kebijakan yang utuh, terintegrasi, dan berkelanjutan sejak pasien masuk rumah sakit, dirawat, serta sampai pasien berada dirumah dan benar-benar tidak membutuhkan perawatan. Tujuan dari penulisan adalah untuk melakukan analisis implementasi discharge planning di Rumah Sakit Umum X Kota Depok. Metodologi yang digunakan adalah pendekatan pilot study yang dilaksanakan dari analisis situasi, pembuatan plan of action, implementasi, evaluasi dan analisis gap dengan menggunakan literature review. Analisis masalah dilakukan melalui diagram fish bone dan analisis prioritas masalah dilakukan dengan menggunakan analisis CARL. Masalah utama adalah belum optimalnya pelaksanaan discharge planning yang terstruktur dan terintegrasi. Implementasi dilaksanakan dengan pendekatan pilot study. Implementasi yang dilakukan adalah pembuatan panduan dan format discharge planning, sosiliasi, uji coba panduan dan format discharge planning, serta evaluasi. Hasil uji coba didapatkan bahwa perawat telah melakukan discharge planning terstruktur dan terintegrasi dengan capaian sebesar 92% berdasarkan pengisian format yang ada. Diperlukan rencana tindak lanjut dari pihak manajemen Rumah Sakit Umum X di Kota Depok untuk menerapkan pelaksanaan discharge planning terstruktur dan terintegrasi. Kata kunci: discharge planning, keperawatan ABSTRACT Implementation of discharge planning is a complete, integrated, and sustainable policy since the patient is admitted to hospital, treated, and until the patient is at home and really does not need treatment. The purpose of writing is to conduct analysis of discharge planning implementation at the Regional General Hospital X in Depok City. The methodology used is pilot study approach which is carried out from situation analysis, plan of action plan, implementation, evaluation and gap analysis by using literature review. Problem analysis was done through fish bone diagram and problem priority analysis was done by using CARL analysis. The main problem is the not yet optimal implementation of structured and integrated discharge planning. Implementation is done by pilot study approach. Implementation is the making of guidance and format of discharge planning, sociation, pilot study and format of discharge planning, and evaluation. The result of the experiment shows that the nurse has done structural and integrated discharge planning with achievement 92% based on the filling of the existing format. A follow-up plan from the management of X General Hospital in Depok City is required to implement a structured and integrated discharge planning. Keywords: discharge planning, nursing DAFTAR PUSTAKA Langhorne, P., Jepsen, B. G., & Larsen, T. (2014). Early home-supported discharge after stroke: a brief report on the practical implementation. International Journal of Rehabilitation Research, 37(2), 192-194. Joint Commission International. (2017). Accreditation Standards For Hospitals, 6th Edition. Diunduh dari https://www.jointcommissioninternational.org/assets/3/7/JCI_Standards_Only_6th_Ed_Hospital.pdf . (2017). Standar Nasional Akreditasi Rumah Sakit Edisi 1. Diunduh dari: http://www.pdpersi.co.id/kanalpersi/manajemen_mutu/data/snars_edisi1.pdf (2012). Instrumen Akreditasi Rumah Sakit Standar Akreditasi Versi 2012 Nordmark, S., Zingmark, K., & Lindberg, I. (2016). Process evaluation of discharge planning implementation in healthcare using normalization process theory. BMC medical informatics and decision making, 16(1), 1. Alper, E., O’Malley, T. A., Greenwald, J., Aronson, M. D., & Park, L. (2015). Hospital discharge and readmission. UpToDate website: Available at: http://www. uptodate. com/contents/hospital-discharge-and-readmission. Accessed August, 14. Yam, C. H., Wong, E. L., Cheung, A. W., Chan, F. W., Wong, F. Y., & Yeoh, E. K. (2012). Framework and components for effective discharge planning system: a delphi methodology. BMC health services research, 12(1), 396. Meyers, L. (2017). The Effectiveness of Discharge Planning in Mental Health: An Integrative Review of Literature. Hunter, T., & Birmingham, J. (2013). Preventing readmissions through comprehensive discharge planning. Professional case management, 18(2), 56-63. Wickramasinghe, N., Kent, B., Moghimi, F. H., Stien, M., Nguyen, L., Redley, B., ... & Botti, M. (2014). Using technology solutions to streamline healthcare processes for nursing: the case of an Intelligent Operational Planning Support Tool (IOPST) solution. In Lean Thinking for Healthcare (pp. 405-430). Springer New York. Horwitz, L. I. (2017). Self-care after hospital discharge: knowledge is not enough. Lancaster, G. A., Dodd, S., & Williamson, P. R. (2004). Design and analysis of pilot studies: recommendations for good practice. Journal of evaluation in clinical practice, 10(2), 307-312. Thabane, L., Ma, J., Chu, R., Cheng, J., Ismaila, A., Rios, L. P., ... & Goldsmith, C. H. (2010). A tutorial on pilot studies: the what, why and how. BMC medical research methodology, 10(1), 1.g Anne Lacey, E. (1994). Research utilization in nursing practice—a pilot study. Journal of advanced nursing, 19(5), 987-995. Bose, T. K. (2012). Application of fishbone analysis for evaluating supply chain and business process-a case study on the St James Hospital. International Journal of Managing Value and Supply Chains (IJMVSC), 3(2), 17-24. Arian, M., Mortazavi, H., TabatabaiChehr, M., Navipour, H., & Vanaki, Z. (2016). Institutionalizing the educational role of nurses by Deming cycle (PDCA). Quarterly Journal of Nursing Management, 4(4), 45-57. Zurlo, A., & Zuliani, G. (2018). Management of care transition and hospital discharge. Aging clinical and experimental research, 1-8. Lowthian, J. A., McGinnes, R. A., Brand, C. A., Barker, A. L., & Cameron, P. A. (2015). Discharging older patients from the emergency department effectively: a systematic review and meta-analysis. Age and ageing, 44(5), 761-770. Arendts, G., MacKenzie, J., & Lee, J. K. (2006). Discharge planning and patient satisfaction in an emergency short‐stay unit. Emergency Medicine Australasia, 18(1), 7-14. Cajanding, R. J. (2017). Effects of a structured discharge planning program on perceived functional status, cardiac self-efficacy, patient satisfaction, and unexpected hospital revisits among filipino cardiac patients: a randomized controlled study. Journal of Cardiovascular Nursing, 32(1), 67-77. Majothi, S., Jolly, K., Heneghan, N. R., Price, M. J., Riley, R. D., Turner, A. M., ... & Fitzmaurice, D. A. (2015). Supported self-management for patients with COPD who have recently been discharged from hospital: a systematic review and meta-analysis. International journal of chronic obstructive pulmonary disease, 10, 853. Collins, S. P., Pang, P. S., Fonarow, G. C., Yancy, C. W., Bonow, R. O., & Gheorghiade, M. (2013). Is hospital admission for heart failure really necessary?: the role of the emergency department and observation unit in preventing hospitalization and rehospitalization. Journal of the American College of Cardiology, 61(2), 121-126. Hesselink, G., Zegers, M., Vernooij-Dassen, M., Barach, P., Kalkman, C., Flink, M., ... & Suñol, R. (2014). Improving patient discharge and reducing hospital readmissions by using Intervention Mapping. BMC health services research, 14, 389-389. Bailey, S., Wilson, G., & Yoong, W. (2015). What factors affect documentation by midwives? A prospective study assessing relationship between length of shift, workload and quality of note keeping. Midwifery, 31(8), 787-792. Wong, E. L., Yam, C. H., Cheung, A. W., Leung, M. C., Chan, F. W., Wong, F. Y., & Yeoh, E. K. (2011). Barriers to effective discharge planning: a qualitative study investigating the perspectives of frontline healthcare professionals. BMC health services research, 11(1), 24 Gonçalves‐Bradley, D. C., Lannin, N. A., Clemson, L. M., Cameron, I. D., & Shepperd, S. (2016). Discharge planning from hospital. The Cochrane Library. Jackson, C., Shahsahebi, M., Wedlake, T., & DuBard, C. A. (2015). Timeliness of outpatient follow-up: an evidence-based approach for planning after hospital discharge. The Annals of Family Medicine, 13(2), 115-122. Brooke, B. S., Stone, D. H., Cronenwett, J. L., Nolan, B., DeMartino, R. R., MacKenzie, T. A., ... & Goodney, P. P. (2014). Early primary care provider follow-up and readmission after high-risk surgery. JAMA surgery, 149(8), 821-828. Miyata, C., Arai, H., & Suga, S. (2015). Characteristics of the nurse manager’s recognition behavior and its relation to sense of coherence of staff nurses in Japan. Collegian, 22(1), 9–17. http://doi.org/10.1016/j.colegn.2013.10.004 MacLeod, L. (2012). A Broader View of Nursing Leadership: Rethinking Manager-Leader Functions. Nurse Leader, 10(3), 57–61. http://doi.org/10.1016/j.mnl.2011.10.003 Hariandja MTE (2002). Manajemen Sumber Daya Manusia. PT. Gramedia Widiasarana Indonesia. Jakarta. Wexley, K. N., & Yukl, G. A. (1984). Organizational behavior and personnel psychology. Richard D. Irwin. Phillips, C. O., Wright, S. M., Kern, D. E., Singa, R. M., Shepperd, S., & Rubin, H. R. (2004). Comprehensive discharge planning with postdischarge support for older patients with congestive heart failure: a meta-analysis. Jama, 291(11), 1358-1367 Hager, J. S. (2010). Effects of a Discharge Planning Intervention on Perceived Readiness for Discharge.